Evaluation of the Accounting Information System for the Iraqi Dates Company Based on the Components of Internal Control - Nihad Mohamed Wahib; Sohad Sabih Alsaffar (Journal of Madenat Alelem University College, 2022)
The paper aims to examine the possibility of evaluating the accounting information system based on the five components of internal control in a way that enhances the quality of accounting information, and makes this a methodology that draws attention to areas of deficiencies, using the results of the evaluation process.The research problem was represented in the weakness of the dates company’s interest in building a methodology that determines how to evaluate the accounting information system through the use of indicators provided by the internal control components, as the aim was to develop and raise the performance level of the policies and procedures of the internal control components that govern the processing of transactions, and a statement of the shortcomings when the components of internal control are not fulfilled, with regard to the credibility of accounting information.As he addressed the purpose of the research through the following hypothesis: The proper and appropriate evaluation by the Iraqi Dates Company to design and implement the accounting information system through the internal control components helps him in drawing up a methodology to deal with and address areas of weakness.While the most important results that were reached through this paper can be mentioned as follows:(A) There are shortcomings in the accounting information system of the company in question, such as the delay in submitting final accounts on time, exaggeration in preparing estimated budgets, and the absence of a control account for a record (Debtors and creditors), and the accounting rule No. (14) Is not applied, and the company does not have an accurate cost system.(B) Weakness in understanding the importance of the components of internal control by the company in question, and the lack of generalization of the rules of professional conduct. There is no department or division for risk management, but it is up to each department of the company, and weakness in the dissemination of control policies and procedures through a brochure distributed to all Administrative levels .The company lacks the introduction of modern technology in the treatment of its operations, and the department does not enjoy the internal audit is independent in the performance of its work.